Effect of build orientation and layer thickness on manufacturing accuracy, printing time, and material consumption of 3D printed complete denture bases. (March 2023) - Song, Shiwei; Zhang, Jie; Liu, Miao; Li, Fenglan; Bai, Shizhu
Abstract: Objectives: To evaluate the influence of build orientation and layer thickness on manufacturing accuracy, material consumption, and printing time of complete denture (CD) bases fabricated using digital light processing (DLP). Methods: The CD base was designed on the basis of a standard maxillary edentulous model. Seventy CD bases were fabricated using a DLP 3D printer (Pro95, SprintRay, USA) and printable CD base material (DENTCA Denture Base II, Dentca, USA) at seven build orientations (0°, labial 45°, labial 90°, posterior 45°, posterior 90°, buccal 45°, and buccal 90°) and two types of layer thicknesses (50- and 100 μm) (n = 5). All test CD bases were digitalized and superimposed on the reference cast by section-based best-fit alignment. For evaluating manufacturing accuracy, deviation analysis was performed to compare the test data with the reference cast using the "3D Compare" in the 3D metrology software. The printing time and material consumption were calculated using slicing software and recorded, respectively. The two-way ANOVA test was used for accuracy evaluation, and the non-parametric test was used to evaluate printing time and material consumption (α = 0.05). Results: Statistically significant differences were found in the manufacturing accuracy (p < 0.001), printing time (p < 0.001), and material consumption (p < 0.001) among the build orientation groups. The labial 45° and labial 90° groups showed the best accuracy. The 90° build orientations required the least material consumption and longest printing time; the labial 45° group consumed the most printing materials; the 0° group required the shortest printing time to fabricate a CD base. Moreover, the layer thickness influenced the printing time (p < 0.001) rather than the accuracy (p = 0.560) and material consumption (p = 1.000). Conclusions: When DLP was used to fabricate the CD bases, the build orientation influenced the manufacturing accuracy, material consumption, and printing time. However, the layer thickness only affected the printing time. Clinical significance: This study suggests that optimizing the build orientation can improve the manufacturing accuracy and reduce the material consumption and printing time of a DLP-printed CD base. The fast-printing setting (100 μm layer thickness) can reduce the printing time without compromising the manufacturing accuracy of the CD base.